Age affects antibody levels and anthelmintic treatment efficacy in a wild rodent. (April 2019) - Clerc, Melanie; Babayan, Simon A.; Fenton, Andy; Pedersen, Amy B.
Abstract: The role of the host immune system in determining parasite burdens and mediating within-host parasite interactions has traditionally been studied in highly controlled laboratory conditions. This does, however, not reflect the diversity of individuals living in nature, which is often characterised by significant variation in host demography, such as host age, sex, and infection history. Whilst studies using wild hosts and parasites are beginning to give insights into the complex relationships between immunity, parasites and host demography, the cause-and-effect relationships often remain unknown due to a lack of high resolution, longitudinal data. We investigated the infection dynamics of two interacting gastrointestinal parasites of wild wood mice ( Apodemus sylvaticus ), the nematode Heligmosomoides polygyrus and the coccidian Eimeria hungaryensis, in order to assess the links between infection, coinfection, and the immunological dynamics of two antibodies (IgG1 and IgA). In an anthelmintic treatment experiment, mice were given a single oral dose of an anthelmintic treatment, or control dose, and then subsequently followed longitudinally over a period of 7–15 days to measure parasite burdens and antibody levels. Anthelmintic treatment successfully reduced burdens of H. polygyrus, but had no significant impact on E. hungaryensis . Treatment efficacy was driven by host age, with adult mice showing stronger reductions in burdens compared to younger mice. We also found that the relationship between H. polygyrus -specific IgG1 and nematode burden changed from positive in young mice to negative in adult mice. Our results highlight that a key host demographic factor like age could account for large parts of the variation in nematode burden and nematode-specific antibody levels observed in a naturally infected host population, possibly due to different immune responses in young vs. old animals. Given the variable success in community-wide de-worming programmes in animals and humans, accounting for the age-structure of a population could increase overall efficacy. Graphical abstract: Image 1 Highlights: Anthelmintic treatment reveals strong force of infection for H. polygyrus in wild wood mice. Anthelmintic treatment is more successful in younger compared to older mice. Relationship between IgG1 and H. polygyrus burden reverts with host age.